Src Homology 2 Domain-Containing Protein Tyrosine Phosphatase Promotes Inflammation and Accelerates Osteoarthritis by Activating β-Catenin - Tao, Tenghui; Luo, Danni; Gao, Chenghao; Liu, Hui; Lei, Zehua; Liu, Wenbin; Zhou, Chuankun; Qi, Dahu; Deng, Zhenhan; Sun, Xuying; Xiao, Jun (Frontiers in Cell and Developmental Biology, 2021)
Osteoarthritis (OA) is a chronic disease characterized by degradation of the cartilage, thickening of the subchondral bone, osteophyte formation. Src homology 2 domain-containing protein tyrosine phosphatase (SHP2), a protein tyrosine phosphatase, was not fully investigated in OA. In this study, we found that SHP2 expression was significantly increased after IL-1β treatment in primary chondrocytes. Next, we unveiled that the inhibition of SHP2 using siRNA could lead to reduced levels of MMP3, MMP13, and an increased level of Aggrecan and Col2a1 in vitro, while the overexpression of which by plasmid displayed in an opposite way. Furthermore, we revealed SHP2 could promote inflammation through activating MAPK and NF-κB pathway, and the knockdown of it restrained Wnt/β-catenin pathway by directly binding to β-catenin. In the mice model of OA, SHP2 knockdown effectively delayed cartilage destruction and rescued the elevated MMP3 and MMP13 levels induced by the DMM surgery. Our study identifies that SHP2 is a potential therapeutic target of OA.